Prevalence of Skin Infections and Regular Personal Hygiene Practices in Ashram School Students: A Cross-Sectional Study - Wasnik, Sumit; Pinto, Violet; Joshi, Sumedha (National Journal of Community Medicine, 2018)
Introduction: It is well known that skin diseases are a major health problem in the pediatric age group and are associated with significant morbidity. Also people in rural areas are often prey to diseases and morbidity due to undesirable health attitudes and behaviors. The present study was conducted to explore the clinical profile of skin infections among ashram school students; to study the association between skin infections and regular personal hygienic practices and to make recommendations based on the study findings. Methodology: A cross-sectional study was done among students of an ashram school located in a rural area of Maharashtra. Results: 19.0 % students had skin infections of which majority were found to be acne and scabies, 24.6% and 22.8% respectively. 31.3% students were not following regular personal hygiene practices. Lack of regular hygienic practices was strongly associated with skin morbidities (p<0.05). Conclusion Regular personal hygiene practices are an important factor associated with skin diseases in the school students, so regular health educational activities on personal hygiene should be carried out for the ashram school students and teachers as well.